2018
DOI: 10.1155/2018/5342624
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Environmental Change, Climate Variability, and Their Role in Prevalence of Mosquitoes among Urban Dwellers in Southern Ghana

Abstract: This study evaluates the extent to which urban residents of Accra and Sekondi-Takoradi (all of southern Ghana) were aware of environment and climate-related variability. A total of 150 questionnaires were given to adults of 40 years and above who lived in the cities for at least 35 years. SPSS version 16 was used to process the data. Results show that all respondents in Accra Metropolitan Area (AMA) and 96% of them in Sekondi-Takoradi Metropolitan Area (STMA) noted the deteriorating vegetation cover over the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Climatic elements such as rainfall and temperature provide enormous support to human societies ( Mensah, 2020 ), however these elements continue to be under serious threat through anthropogenic activities such as urban sprawl ( Mattah et al., 2018 ; Li et al., 2017 ). The more urban population increases, the more space is needed to house these numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climatic elements such as rainfall and temperature provide enormous support to human societies ( Mensah, 2020 ), however these elements continue to be under serious threat through anthropogenic activities such as urban sprawl ( Mattah et al., 2018 ; Li et al., 2017 ). The more urban population increases, the more space is needed to house these numbers.…”
Section: Discussionmentioning
confidence: 99%
“…, 2015 ) . While a lot of researches have been conducted on urban sprawl effects and climate change worldwide ( Liu and Niyogi, 2019 ; Mansouri Daneshvar et al.2019 ; Alqurashi and Kumar, 2017 ; Chapman et al., 2017 ; Deng et al., 2013 ), very few studies have been conducted in Ghana with the past research foci being on the extent of sprawl, green space reduction and policy implementation to reduce urban sprawl ( Cobbinah et al., 2019 ; Daniels et al., 2018 ; Mensah, 2020 ; Mattah et al., 2018 ), livelihood and ecological management ( Afriyie et al., 2019 ), environmental sustainability ( Yiran, 2020 ), and loss of agricultural lands ( Abass et al., 2018 ; Cobbinah and Aboagye, 2017 ). Amazingly, no preceding work has scrutinized the impact of urban sprawl on microclimate in the Greater Accra region and its Ga East Municipality in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Impacts of climate change are found in terms of increasing temperature, decreasing the number of rainy days, rainfall variations, frequent droughts, severe heat waves, and evidence of periodic floods. Such trends threaten crop yields and risk the food security of poorer countries where agriculture is rain-fed [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 2003, stroke was the sixth most common cause of death in the Ashanti region of Ghana (Cappuccio et al, 2004;Agyemang, 2006). Mattah et al, (2018), also identified that geography affects the health of humans by studying two metropolitan areas (Accra and Takoradi) in southern Ghana. This study also identified that citizens in these areas are aware of how their environment is affecting their health.…”
Section: Introductionmentioning
confidence: 99%